The conservative modernization of agriculture and the pathogenic transformation of space: Poisoning and death by use of pesticides in Espírito Santo - Aguiar Junior, Paulo Cesar; Barcellos Neto, Christovam de Castro (Geografares, 2018)
The present article aims to expose the essential relationship between the conservative modernization of agriculture, its system of techniques and the pathogenic transformation of space. Therefore, we seek to reveal the nuances of conservative modernization in Brazil and Espírito Santo, through the analytical categories of systems object and systems of action. From this perspective, we present an overview of the poisoning and death resulting from the use of pesticides, from 2007 to 2014, en Espírito Santo. For this, we used the spatialization of the data, made available by the official information systems, in order to construct a set of maps and graphs that evidenced the pathogenic content of the space.Keywords: Conservative modernization; systems object and actions; pathogenic space.